Aktualne problemy bankowości spółdzielczej - Pietraszkiewicz, Krzysztof (Current Problems of Co-Operative Banking, 2005)
Recently, co-operative banks have successfully reinforced their market position as a result of own efforts by bankers and boards, and also due to policies of the central bank and the government. Those efforts resulted, among other things, in the capital and organizational strengthening of co-operative banks, and in the higher service quality. Further dynamic development of co-operative banking requires first of all the reduction of operational costs, the increase in work productivity, and better exploiting of advanced teleinformation technologies. Additional marketing activities, risk management methods (among other things applying the available databases of Credit Information Bureau, Business Information Bureau, and so forth), and taking advantage of opportunities offered by the Single Market of the European Union are required in order to further reinforce the co-operative banks in the financial services market
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1068, s. 9-12